Contours of Feminist Political Ecology - Harcourt, Wendy; Agostino, Ana; Elmhirst, Rebecca; Gómez, Marlene; Kotsila, Panagiota (Gender, Development and Social Change,, 2023)
This open access book sets out the contours of feminist political ecology (FPE) as a major contribution to ongoing debates in the field. In an innovative methodological twist, the edited book engages the reader in conversations that have emerged from the multi-sited and cross-generational dialogues of the Well-Being Ecology Gender cOmmunities (WEGO) network over the last four years. The conversations explore topics that range from climate change and extractivism, to body politics and health, degrowth, care and community well-being. The authors reflect on their collective learning process as they map out the new directions of FPE research and analysis. The chapters highlight WEGO transnational/transdisciplinary conversations with local communities, social movements and different academic spaces. The book foregrounds the ethics of doing feminist work inside and outside academe and brings to life the importance of doing reflexive research aware of situated historical and contemporarygeographical contours of power. Wendy Harcourt is Professor of Gender, Diversity and Sustainable Development at the International Institute of Social Studies of the Erasmus University Rotterdam in The Hague, The Netherlands and was Coordinator of the WEGO Innovative Training Network (2018-2022). Ana Agostino is Lecturer at the Faculty of Culture at the University CLAEH, Uruguay, and at FLACSO. Rebecca Elmhirst is Professor of Human Geography at the University of Brighton, UK. Marlene Gómez is PhD candidate of the WEGO Innovative Training Network at the Freie Universität Berlin, Germany. Panagiota Kotsila is 'Juan de la Cierva' Fellow at the Institute for Environmental Science and Technology (ICTA), at the Universitat Autònoma de Barcelona, Spain, and Coordinator of the Political Ecology research line at the Barcelona lab for Urban Environmental Justice and Sustainability (BCNUEJ). .